In vitro study of the pulp chamber temperature rise during light-activated bleaching (Journal of Applied Oral Science, 2008)
This study evaluated in vitro the pulp chamber temperature rise induced by the light-activated dental bleaching technique using different light sources. The root portions of 78 extracted sound human mandibular incisors were sectioned approximately 2 mm below the cementoenamel junction. The root cavities of the crowns were enlarged to facilitate the correct placing of the sensor into the pulp chamber. Half of specimens (n=39) was assigned to receive a 35% hydrogen peroxide gel on the buccal surface and the other halt (n=39) not to receive the bleaching agent. Three groups (n=13) were formed for each condition (bleach or no bleach) according to the use of 3 light sources recommended for dental bleaching: a light-emitting diode (LED)laser system, a LED unit and a conventional halogen light. The light sources were positioned perpendicular to the buccal surface at a distance of 5 mm and activated during 30 s. The differences between the initial and the highest temperature readings for each specimen were obtained, and, from the temperature changes, the means for each specimen and each group were calculated. The values of temperature rise were compared using Kruskal-Wallis test at 1% significance level. Temperature rise varied significantly depending on the light-curing unit, with statistically significant differences (p;0.01). When the bleaching agent was applied, there were significant differences among groups (p